Perilaku Komunikasi Remaja Pengguna Game Online - Rifqi Fauzi (Communicative : Jurnal Dakwah dan Komunikasi, 2021)
This study aims to describe the communication behavior of teenagers using online games and to determine the factors that influence the communication behavior of teenagers using online games. This study uses a qualitative method. The data collection techniques used were through observation, in-depth interviews, and documentation studies. The data analysis technique used in this study is a qualitative descriptive analysis technique. Meanwhile, the validity of the data was checked using the source triangulation technique. The results of this study indicate that 1) The communication behavior of online game users occurs because of habitual factors and emotional factors that occur in themselves. This behavior refers to changes in attitudes, behavior and also changes in conveying information. 2) There are six indicators of factors that influence the communication behavior of teenagers using online games, including the following: Lack of attention from those closest to them, depression, lack of control, lack of activity, environment and parenting.